2012
DOI: 10.1002/tox.21769
|View full text |Cite
|
Sign up to set email alerts
|

The roles of endoplasmic reticulum stress and mitochondrial apoptotic signaling pathway in quercetin‐mediated cell death of human prostate cancer PC‐3 cells

Abstract: Prostate cancer has its highest incidence and is becoming a major concern. Many studies have shown that traditional Chinese medicine exhibited antitumor responses. Quercetin, a natural polyphenolic compound, has been shown to induce apoptosis in many human cancer cell lines. Although numerous evidences show multiple possible signaling pathways of quercetin in apoptosis, there is no report to address the role of endoplasmic reticulum (ER) stress in quercetin-induced apoptosis in PC-3 cells. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 46 publications
6
60
0
Order By: Relevance
“…Analogous to previous studies in human prostate cancer cells (24,(28)(29)(30), the present study demonstrated that genistein, luteolin and quercetin induced apoptosis in DU145 cells. Thus, genistein, luteolin and quercetin may inhibit the growth of prostate cancer cells through the induction of cell cycle arrest and apoptosis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Analogous to previous studies in human prostate cancer cells (24,(28)(29)(30), the present study demonstrated that genistein, luteolin and quercetin induced apoptosis in DU145 cells. Thus, genistein, luteolin and quercetin may inhibit the growth of prostate cancer cells through the induction of cell cycle arrest and apoptosis.…”
Section: Discussionsupporting
confidence: 64%
“…Similarly, previous studies have demonstrated that flavonoids inhibit cell growth by inducing S phase cell cycle arrest in prostate cancer cells (19)(20)(21). Flavonoids have also been documented to arrest cell-cycle progression at G0/G1 and G2/M in prostate cancer cells (22)(23)(24). These results indicate that flavonoids may block cell growth at multiple stages of the cell cycle (25).…”
Section: Discussionmentioning
confidence: 53%
“…Two major phenomena concerning apoptosis occured that are related to, cleavage of cas 3 and parp proteins, determined in the Q-Cntrl groups at 6 and 12 h ( Figure 3C and 3D). Cas 3 is the most common executioner caspase [31] and extinguishes cell by cleaving parp [32]. Our results clearly demonstrated that quercetin caused cell death at high concentration through cas 3 dependent apoptotic pathway ( Figure 3C).…”
supporting
confidence: 55%
“…For ΔΨ m measurement, cells were isolated and re-suspended with 500 μl of 3,3'-dihexyloxacarbocyanine iodide (DiOC 6 ) (Sigma Chemical Co.) (4 μmol/l) and maintained in the dark for 30 minutes. After incubation, all samples were analyzed by flow cytometry as described previously (33)(34)(35). in vivo 31: 1103-1114 (2017) Measurements of caspase activities.…”
Section: Methodsmentioning
confidence: 99%